EFFECT OF VEHICLE QUALITY AND SPEED ON THE IMPACT CHARACTERISTICS OF AN OVERPASS BRIDGE PIER - Shijie Wang; Quansheng Sun; Jianxi Yang (Civil Engineering Journal, 2020)
To study the impact of the mechanical characteristics of heavy trucks on piers under different masses and speeds, a new equivalent simplified model of heavy trucks is proposed in this paper. The reliability of the calculation model is verified by studying the pier of the G1011 Ha-Tong high-speed K302+095 separated overpass, which was subjected to impact by a heavy truck. A finite element model of a heavy truck and a pier is established using the finite element software ABAQUS, and the influence of heavy truck load and impact speed on the impact force and pier stress is analysed. Results show that the peak of impact force increases with the increase in the mass and impact speed of heavy trucks. The high-stress area of the pier is concentrated in the root and the impact position, and an inclined through-crack is formed at 45° with the pier axis. The results also reveal the influence law of the quality of heavy trucks and impact speed on the impact force and stress of the pier and provide a new theoretical basisfor the anti-collision design of piers and the limitation of current specifications on the high-speed impact of heavy trucks on piers.